Induksi Propagul Kultur Nodus Tanaman Anggur (Vitis vinifera) varietas Prabu Bestari pada Berbagai Konsentrasi ZPT BA dan NAA - WIRDASARI, DINI; DWIYANI, RINDANG; DARMAWATI, IDA AYU PUTRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.1, Januari 2022, 2022)
Propagule Induction of Node Culture of Grape ( Vitis vinifera ) varieties Prabu Bestari at Various Concentration of BA and NAA Propagation of grape seeds still uses conventional methods such as cuttings and grafting. In vitro culture technology can be a solution for plant propagation techniques that using small explants and in small quantities but capable to producing large amounts of seeds. Propagules are new formations that arise from explant tissue, can be in the form of shoots or callus that can occur through direct or indirect organogenesis. The aim of the research was to obtain the best culture medium in the formation of propagules. The research was conducted in two stages, the first was propagule induction and the second was subculture. The research used a Completely Randomized Design. Propagule induction was used a factor with combination of BA and NAA. The levels use of ZPT BA are: 2 ppm, 4 ppm, 6 ppm and the levels use of ZPT NAA are: 1 ppm, 3 ppm, and 5 ppm. The total combination treatment was 9 treatments and the addition of treatment K0 (control). Each treatment was repeated 3 times for a total of 30 experimental units. The subculture medium used was WPM + 1 ppm TDZ. The results showed that MS treatment with a combination of ZPT BA and NAA succeeded in forming propagules in the form of meristemoids and shoots. K3 (MS + 2 ppm BA + 5 ppm NAA) was the treatment that gave the best response to the percentage of meristemoid formation of 100%. K4 (MS + 4 ppm BA + 1 ppm NAA) was the treatment that succeeded in inducing 33.3% shoots.